Ethical Crossroads of Genetic Engineering in Huxley's Brave New World (SCHOLARS: Journal of Arts & Humanities, 2026)
This article critically reads Aldous Huxley’s novel Brave New World to analyze how it portrays the futurity of human society that is contemporarily relying greatly on technologies. Progress of science and technology has tremendously upheld the human society on the one hand, but it has simultaneously desensitized natural instincts of human beings, particularly through genetic engineering on the other. Huxley’s narrative manifests that the promotion of science and technology has turned human life topsy-turvy playing a spoil sport to detach human beings from natural world. Unlike natural way of reproduction, human beings are artificially produced in a lab like manufactured goods, and they are socially conditioned. Their individuality is suppressed and a drug (Soma) is given to provide artificial happiness. Human beings are produced in hatcheries. They lack moral values and emotions. Meanwhile, the savage lifestyle and wilderness meet their tragic end in the artificial society of the World State, fabricated by the genetically modified citizens. The narrative functions as ethical mirrors, reflecting society’s desire to commodify human life. It echoes current unchecked issues of manipulating of human genome unethically. Using theoretical ideas from ecocriticism, particularly the idea of Ecological Self by Arne Naess, this article explores how human emotions, happiness and pain are relatively interconnected with nature, to make human life stable and equilibrium with natural ecology. The finding shows that technological advancement led by consumer society does not only deteriorate nature but also manipulates natural life course of human beings towards mechanized components of a sterile and emotionless society. This article contributes to understanding ethical responsibilities in the field of genetic engineering and psychological conditioning.